THE SHANGHAI COOPERATION ORGANIZATION: N ANALYSIS OF ITS SUSTAINABILITY AND DEVELOPMENT (On the Outcome of the Meeting of the SCO Council of Heads of Government. Bishkek, September 2004) - ARUNOVA, Mariam; GORIUNKOV, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2004)
The meeting of the Council of Heads of Government (CHG) of the Shanghai Cooperation Organization member states held on 23 September 2004 in the Kyrgyzstan capital declared that the forma-ion stage of this structure has essentially reached its conclusion. In so doing, it was noted that many of the Organization’s mechanisms were launched in a relatively short space of time. We will remind you that the heads of the six member states (Kazakhstan, China, Kyrgyzstan, Russia, Tajikistan, and Uzbekistan)signed a declaration on the creation of this structure at their meeting in Shanghai on 15 June, 2001. It took just over three years to set it up and define the operating procedure for its standing bodies—the Secretariat and Executive Committee of the Regional Antiterrorist Center. What is more, the activity of these bodies has been furnished with a legal, financial, and organizational base, they have been staffed, and relations have been established with the states in which they will be located—China and Uzbekistan.